Inhibition of Cervical Cancer Cell Migration by Human Wharton’s Jelly Stem Cells - Snwr Sabir Mohammad; Masoud Maleki (Research in Molecular Medicine)
Background: One of the most prevalent malignancies to strike women, both in Iran and globally, is cervical cancer. Metastasis, which is a significant cause of mortality, is one of the most significant pathological processes of this cancer. Therefore, preventing the migration of cancer cells may be a useful therapeutic approach. The aim of this work was to investigate the impact of conditioned media and human Wharton's jelly stem cells (hWJSCs) on the migration and growth of the cervical cancer cell line Hela as well as the in vitro mRNA expression of genes involved in metastasis. Methods: After primary culture, cellular extract and conditioned medium of hWJSCs were prepared. The viability of cervical cancer cells was investigated by MTT assay after treatment with cellular extract and conditioned medium of hWJSCs. Moreover, the anti-migratory effects of cellular extract and conditioned medium of hWJSCs on the cervical cancer cells were evaluated by wound‐healing migration assay. Finally, the mRNA expression of migration-related genes (E-cadherin and Vimentin) was detected by real-time PCR. Results: Our results indicated that the cellular extract and conditioned medium of hWJSCs (with 32% concentration) inhibited the proliferation of 100% and 20% of Hela cancer cells, respectively. In addition, the cellular extract and conditioned medium of hWJSCs significantly decreased morphological alteration and migration of the cancer cells. The cellular extract and conditioned medium of hWJSCs modified the expression of Vimentin and E-cadherin genes to inhibit the cancer cell migration (p<0.05). However, the cellular extract indicated significantly profound inhibitory effects on the cervical cancer cells compared to the conditioned medium. Conclusions: Our study demonstrated that the cellular extract and conditioned medium of hWJSCs inhibit the proliferation and migration of cervical cancer cells through the modification of migration-related gene expression. However, further in vitro and in vivo studies are required for more accurate results.